The impact of geopolitical risk on cash holdings policy: evidence from an emerging market - AKSOY HAZIR, ÇAĞRI; TAN, ÖMER FARUK (My University, 2023)
Purpose: This study aims to examine whether geopolitical risk (GPR) impacts the cash holdings behavior of 210 Turkish firms between 2005 and 2019. The authors choose Turkey as a country of interest because Turkey has an important place in terms of geographical location and serves as a bridge between Europe and Asia. Considering the prominent role that can play in decision-making processes, the authors thought that analyzing the impact of GPR on the cash holdings determinants of Turkish firms would be important and interesting. A widely accepted view is that GPRs play an important role in the economic decisions of emerging countries, such as Turkey. Design/methodology/approach: The authors examine models with fixed effects (FE), random effects (RE) and pooled ordinary least squares (POLS), respectively. First, the authors analyzed whether POLS, FE or RE would be the most appropriate model. According to the F-test and the Breusch–Pagan LM test, the FE and the RE models are more suitable than POLS. Then, according to the Hausman test results, the authors found that FE is this study\"s most appropriate model. After determining the validity of FE, the diagnostics tests of heteroscedasticity, autocorrelation and serial correlation tests are examined. Due to the presence of these problems, Driscoll and Kraay\"s (1998) test, which is the robust standard error estimator, is used. Findings: The authors find a positive relationship between GPR and cash holdings after controlling firm-level control variables. Firms faced with uncertainty prefer to hoard cash as a precautionary measure. In keeping with real options theory, firms postpone the investments of firms under uncertain conditions. The use of alternative measurements for GPR and cash holdings ensures the validity of our results. The authors\" research reveals that investors and politicians should pay more attention to the influence of GPR on the determinants of the cash holdings of firms. Research limitations/implications: There are limitations for this study, but this study may provide opportunities for further studies. First, this study has only data from Turkey. This situation mitigates cross-country effects. In future studies, the number of firms, countries of focus and time span can be expanded. Second, this study does not consider the period of coronavirus disease 2019 (COVID-19) that increased risk and uncertainty worldwide. Further studies may consider the impact of COVID-19 and geographical risks relating to cash holdings. Third, the authors try to choose more relied independent and control variables. Practical implications: The authors\" results provide some insights that are relevant to practitioners and policymakers. Managers need to consider GPR in managers\" financial decisions based on managers\" firm-specific characteristics. Turkish policymakers should target improving policies to alleviate the negative effects of GPRs. Regulators should postulate more encouraging policies to firms in an environment of GPR. Regulators can give firms more time to understand and analyze the GPRs and the impacts of GPRs to adjust regulators\" day-to-day activities. Originality/value: There are fewer studies in the literature that analyzed the relationship between GPR and cash holdings. This study aims to full this gap in the literature.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Labor Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞ FİNANSI; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS, FINANCE; İşletme, Yönetim ve Muhasebe (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Finans; Business, Management and Accounting (miscellaneous); Social Sciences & Humanities; Finance; Cash holdings; Emerging market; Geopolitical risk index; Precautionary motive